Аutomated method for determining the etch pits density on crystallographic planes of large semiconductor crystals - Pekar, G.S.; Singaevsky, А.А.; Singaevsky, А.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
A method for express automatic evaluation of the dislocation density on the crystal surfaces has been developed. The work involves creation of a software that allows automatical determining the number of etch pits with a defined geometric shape, which are seen in the microscope view field, and calculation of the density of those etch pits. In addition, adaptation of a metallographic microscope for the above measurements has been made. The developed method can be used to greatly speed up the maping of etch pits density over the area of large crystals. For example, duration of about 400 measurements of etch pits density made in various sites of 330×150 mm surface of the optical germanium crystal plate and of maping the etch pits distribution over this surface made by the developed method is about 40 min, while duration of the same measurements made by the traditional method for visual counting the number of etch pits seen in the eyepiece of the microscope is several dozens of hours. Use of the described method has allowed us to determine the geometric position of maximum internal stress in large optical germanium plates grown by horizontal unidirectional crystallization. This method has been already included in the metrological complex of serial production of large-area plates made of Na-doped optical germanium – a new material of infrared technique, developed and introduced into production at the V. Lashkaryov Institute of Semiconductor Physics, NAS of Ukraine.